Directed Evolution Pipeline for the Improvement of Orthogonal Translation Machinery for Genetic Code Expansion at Sense Codons - Biddle, Wil; Schwark, David G.; Schmitt, Margaret A.; Fisk, John D. (Frontiers in Chemistry, 2022)
The expansion of the genetic code beyond a single type of noncanonical amino acid (ncAA) is hindered by inefficient machinery for reassigning the meaning of sense codons. A major obstacle to using directed evolution to improve the efficiency of sense codon reassignment is that fractional sense codon reassignments lead to heterogeneous mixtures of full-length proteins with either a ncAA or a natural amino acid incorporated in response to the targeted codon. In stop codon suppression systems, missed incorporations lead to truncated proteins; improvements in activity may be inferred from increased protein yields or the production of downstream reporters. In sense codon reassignment, the heterogeneous proteins produced greatly complicate the development of screens for variants of the orthogonal machinery with improved activity. We describe the use of a previously-reported fluorescence-based screen for sense codon reassignment as the first step in a directed evolution workflow to improve the incorporation of a ncAA in response to the Arg AGG sense codon. We first screened a library with diversity introduced into both the orthogonal Methanocaldococcus jannaschii tyrosyl tRNA anticodon loop and the cognate aminoacyl tRNA synthetase (aaRS) anticodon binding domain for variants that improved incorporation of tyrosine in response to the AGG codon. The most efficient variants produced fluorescent proteins at levels indistinguishable from the E. coli translation machinery decoding tyrosine codons. Mutations to the M. jannaschii aaRS that were found to improve tyrosine incorporation were transplanted onto a M. jannaschii aaRS evolved for the incorporation of para-azidophenylalanine. Improved ncAA incorporation was evident using fluorescence- and mass-based reporters. The described workflow is generalizable and should enable the rapid tailoring of orthogonal machinery capable of activating diverse ncAAs to any sense codon target. We evaluated the selection based-improvements of the orthogonal pair in a host genomically engineered for reduced target codon competition. Using this particular system for evaluation of arginine AGG codon reassignment, however, E. coli strains with genomes engineered to remove competing tRNAs did not outperform a standard laboratory E. coli strain in sense codon reassignment.